2020
DOI: 10.1186/s12889-020-09053-1
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and stigma of latent tuberculosis infection in Brazil: implications for tuberculosis prevention strategies

Abstract: Background: Tuberculosis (TB) elimination requires treatment of millions of persons with latent M. tuberculosis infection (LTBI). LTBI treatment acceptance depends on population-wide TB knowledge and low stigma, but limited data are available on the relationship between stigma and knowledge. We assessed knowledge of TB disease and LTBI throughout Brazil and examined their association with TB stigma and incidence. Methods: We performed a nationwide survey with multi-stage probability design through AmericasBaro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 19 publications
2
6
0
4
Order By: Relevance
“…Similar to findings elsewhere in the Netherlands [26] and Brazil [27], TB stigma was a major barrier to LTBI services. Increased knowledge and awareness of LTBI led to an increase in expressed stigma [27].…”
Section: Plos Global Public Healthsupporting
confidence: 79%
See 1 more Smart Citation
“…Similar to findings elsewhere in the Netherlands [26] and Brazil [27], TB stigma was a major barrier to LTBI services. Increased knowledge and awareness of LTBI led to an increase in expressed stigma [27].…”
Section: Plos Global Public Healthsupporting
confidence: 79%
“…Similar to findings elsewhere in the Netherlands [26] and Brazil [27], TB stigma was a major barrier to LTBI services. Increased knowledge and awareness of LTBI led to an increase in expressed stigma [27]. This was also the case in our setting were HHCs did not want the health worker teams to carry out any procedures from outside the house as they expressed fear of stigma from neighbors.…”
Section: Plos Global Public Healthsupporting
confidence: 79%
“…If replicated in other settings, a sex difference in LTBI would be informative from a health equity standpoint. TB disease stigma persists in Brazil, with higher stigmatization paradoxically among those with knowledge of LTBI ( Rebeiro et al ., 2020 ). Identifying and dismantling structural barriers that reinforce stigma can decrease the active TB disease burden – this can be achieved partly through early recognition, education, and treatment of LTBI.…”
Section: Discussionmentioning
confidence: 99%
“…A Brazilian study [17] investigating stigma towards TB in the general population found that 57% of the participants knew that LTBI could occur, and 90% would seek treatment for it, suggesting that knowledge and stigma should not be an important barrier in our population. This factor should be better explored, along with other possible issues such as economic barriers for health care seeking, difficulties pertaining to absences from work and risk perception.…”
Section: Discussionmentioning
confidence: 99%